2021
DOI: 10.1007/s10198-021-01357-2
|View full text |Cite
|
Sign up to set email alerts
|

Health effects from heat waves in France: an economic evaluation

Abstract: Background Scarcity of data on the health impacts and associated economic costs of heat waves may limit the will to invest in adaptation measures. We assessed the economic impact associated with mortality, morbidity, and loss of well-being during heat waves in France between 2015 and 2019. Methods Health indicators monitored by the French national heat wave plan were used to estimate excess visits to emergency rooms and outpatient clinics and hospitalizations for heat-related causes. Total excess mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 53 publications
1
28
0
3
Order By: Relevance
“…€653 million (PM 2.5 ) and €179 million (NO 2 ). It thus approaches those obtained in other studies comparing independent vs. joint processing of uncertainties (Adélaïde et al, 2021a;.…”
Section: Independent Processing Of Uncertaintiessupporting
confidence: 84%
“…€653 million (PM 2.5 ) and €179 million (NO 2 ). It thus approaches those obtained in other studies comparing independent vs. joint processing of uncertainties (Adélaïde et al, 2021a;.…”
Section: Independent Processing Of Uncertaintiessupporting
confidence: 84%
“…13 A study in France between 2015 and 2019 found that the economic impact of increased outpatient and emergency room visits and hospitalizations, mortality, and restricted activity days due to heat waves amounted to €25.5 billion, mainly in mortality (€23.2 billion), minor restricted activity days (€2.3 billion), and morbidity (€0.031 billion). 14 Increased central body temperature causes vasodilatation, increased sweating, increased heart and respiratory rates, increases in oxidative stress, inflammation, muscle breakdown, and changes in coagulation. For example, a review of 57 studies found that heat exposure and air pollution were associated with adverse birth outcomes, including pre-term birth, low birth weight, and stillborn 15 A comprehensive study by the Environmental Protection Agency (EPA) found that there are four socially vulnerable populations which are disproportionally impacted by increased heatrelated illnesses and mortality associated with climate change: African Americans, who are more likely than others to live in areas with the highest projected increases in temperature-related mortality.…”
Section: Increasing Temperaturesmentioning
confidence: 99%
“…Globally, in 2018, there was an increase of 220 million heatwave exposure events versus the average number of events in 1986–2005 13 . A study in France between 2015 and 2019 found that the economic impact of increased outpatient and emergency room visits and hospitalizations, mortality, and restricted activity days due to heat waves amounted to €25.5 billion, mainly in mortality (€23.2 billion), minor restricted activity days (€2.3 billion), and morbidity (€0.031 billion) 14 …”
Section: Effects Of Climate Change and Increased Exposure To Pollutan...mentioning
confidence: 99%
“…Based on the characteristics of the above methods, this study adopted the willingness-to-pay (i.e., value of statistical life) method to calculate the economic loss of the health endpoints of heat-related death. Due to the lack of VSL value related to high temperature, Adélaïde et al analyzed health-related economic impacts in 96 French metropolitan areas during heat waves from 2015 to 2019 and proposed that some values such as VSL in the context of air pollution could be relied upon health-related economic losses estimation ( 27 ). Although the VSL of air pollution is available from various research, there is little information of a ready estimate for Wuhan City found from published works up to now.…”
Section: Methodsmentioning
confidence: 99%